Pilihan bahasa dan lingua franca suku kaum di Sarawak (Jurnal Bahasa, 2022)
The aim of this research is to identify the the common language or lingua franca of Malay, Iban, Chinese and Melanau ethnics groups in Sarawak. There are several ethnic groups in Sarawak, the member of each communicating among themselves in their own language. At the same time, the ethnic groups also share and use a common language or languages to communicate with speakers of other languages spoken within the state. A lingua franca is approriate, comprehendible and does not give rise to communication problems. It is used in everyday life and will be automatically selected and used by speakers from different ethnic groups both in formal and informal situations. An analysis of the choice of language by Malay, Iban, Chinese and Melanau respondents in Sarawak shows that the Iban language and the Sarawak Malay dialect are most often chosen as the lingua francas of Sarawak. The Iban language is used in informal settings while the Sarawak Malay dialect is used in formal settings.